Getting started with oracle VM virtualbox : build your own virtual envinronment from scratch using virtualbox - Dash, Pradyumna (Professional expertise distilled., 2013)
A step-by-step guide that will show you how to install, configure, and manage VirtualBox. This book is for system administrators, technical architects, and virtualization enthusiasts who want to learn how to set up a virtual machine. Knowledge of the Linux environment is expected. Prior experience with VirtualBox or knowledge of virtualization is not required.